Engineering psychology and cognitive ergonomics : cognition and design : 17th International Conference, EPCE 2020, held as part of the 22nd HCI International Conference, HCII 2020, Copenhagen, Denmark, July 19-24, 2020, Proceedings.: cognition and design : 17th International Conference, EPCE 2020, held as part of the 22nd HCI International Conference, HCII 2020, Copenhagen, Denmark, July 19-24, 2020, Proceedings. Part II (2020) - Unknown
No abstract available